Coagglomeration of Formal and Informal Industry : Evidence from India - Mukim, Megha (World Bank, Washington DC, 2013)
A large and growing informal sector is a major feature of developing countries. This paper analyzes coagglomeration patterns between formal and informal manufacturing enterprises in India. It studies (a) the causes underlying these patterns and (b) the positive externalities, if any, on the entry of new firms. The analysis finds that buyer-supplier and technology linkages explain much of formal-informal coagglomeration. Also, within-industry coagglomeration matters mostly to small- and medium-sized formal firm births. Traditional measures of agglomeration remain important in explaining new industrial activity, whether in the formal or the informal sector.